2009
DOI: 10.1002/jmri.21912
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diffusion time on short‐range hyperpolarized 3He diffusivity measurements in emphysema

Abstract: Purpose:To characterize the effect of diffusion time on short-range hyperpolarized 3 He magnetic resonance imaging (MRI) diffusion measurements across a wide range of emphysema severity. Materials and Methods:3 He diffusion MRI was performed on 19 lungs or lobes resected from 18 subjects with varying degrees of emphysema using three diffusion times (1.6 msec, 5 msec, and 10 msec) at constant b value. Emphysema severity was quantified as the mean apparent diffusion coefficient (ADC) and as the percentage of pix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 27 publications
8
20
0
Order By: Relevance
“…It also suggests that R may not be as sensitive to early changes in lung morphology but may become very sensitive once the disease exceeds a critical point. A DC BC and l og(L x ), as previously described (18,28), are strongly correlated (product moment correlation coefficient: 0.85, P ϭ 0.002), and A DC BC monotonically increases as l og(L x ) increases, so we anticipate that the ADC, like l og(L x ), will be sensitive to early changes in airway structure and, thus, suitable for early disease detection.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…It also suggests that R may not be as sensitive to early changes in lung morphology but may become very sensitive once the disease exceeds a critical point. A DC BC and l og(L x ), as previously described (18,28), are strongly correlated (product moment correlation coefficient: 0.85, P ϭ 0.002), and A DC BC monotonically increases as l og(L x ) increases, so we anticipate that the ADC, like l og(L x ), will be sensitive to early changes in airway structure and, thus, suitable for early disease detection.…”
Section: Discussionsupporting
confidence: 58%
“…We based this hypothesis on three suppositions. The first is that ADC will be a sensitive measure of alveolar destruction and that it can be used to grade tissue destruction radiographically, comparable to the use of chord length (L x ) to grade emphysema using histological samples (18,33,52). The second supposition is that HP MRI fractional ventilation is a sensitive measure of the airflow obstruction induced by emphysema with the potential to determine contrasts significant enough to differentiate diseased from normal lung segments (13,45).…”
Section: ϫ5mentioning
confidence: 99%
“…This is particularly the case when attempting to quantify morphological changes in important clinical questions such as early onset of emphysema [27] or the alveolarization of developing lungs [29], where, far-reaching clinical conclusions have been drawn about the nature of the micro-structural modifications caused by disease and growth. The results and models presented in this work may help in the development of a more realistic theoretical framework for in vivo lung morphometry using 3 He diffusion MR.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for the absence of this dependence is not apparent, but may be due in part to extrapolating results obtained for a single diffusion time D = 1.8 ms [10] to a wider range of diffusion times in which the model has not been tested. The omission of this dependence is particularly significant since the cylinder model has been used to draw important clinical conclusions from the interpretation of diffusion data obtained at diffusion times up to 10 ms [27] and conclusions about the nature of structural changes in emphysema were extracted based on the assumption of a diffusion time independence of D L0 . Furthermore, the values of D L0 predicted by the cylinder model are also significantly smaller than those obtained with both the branching duct model and the long duct models for D < 4 ms.…”
Section: Longitudinal Diffusivitymentioning
confidence: 99%
“…During the 5-ms diffusion time in our experiments, a gas atom would most likely encounter one or more tissue walls that restrict motion without drifting outside of one alveolar duct. Although discussion on the importance of diffusion time and modeling has been debated extensively in the literature (48,49), experiments with 3 He have demonstrated that the diffusion time has a relatively small effect on the measured ADC compared with differences seen as a result of airspace enlargement (50). In the future we will explore multiple b-value diffusion experiments with xenon.…”
Section: Direct Comparison Ofmentioning
confidence: 98%